DESAIN DAN IMPLEMENTASI SISTEM INFORMASI MONITORING PENGGUNAAN DAYA LISTRIK DENGAN FITUR MAP MODELLING UNTUK MENDUKUNG PROGRAM GREENCAMPUS DI UNIVERSITAS TELKOM - Hartaman, Aris (Direktorat Penelitian dan Pengabdian Masyarakat, Universitas Telkom, 2024)
Telkom University (Tel-U) is one of the educational institutions that is committed to running the Green Campus program. In carrying out the Green Campus program, there is a ranking standard adopted by the Telkom University campus, namely UI Green metric. One of the standards is related to energy and climate change, namely related to electricity use on campus. And in 2023, electricity use on campus will still be high and there are no tools to monitor electricity use. In this research, a monitoring device has been created in the form of an information system for monitoring electrical power usage using map modeling. This research was conducted at the Selaru Telkom University building. This information system uses a website to display the results of monitoring electricity usage sent by the microcontroller via Google Firebase as database storage which will then be processed to produce images in the form of building map modeling. After obtaining the data, the modeling will show in color the floor on which floor the largest electricity users in the building are located. By using this information system, we can see how much electricity is used in the Selaru building and we can make decisions in carrying out activities to make electricity use more efficiently